An Unusual Case of Pleuropulmonary Blastoma in a Child with Jejunal Hamartomas - Chantal Lucia-Casadonte; Sakil Kulkarni; Ricardo Restrepo; Ruben Gonzalez-Vallina; Carole Brathwaite; Edward Y. Lee (Hindawi Limited, 2013)
We report a rare case of 9-month-old girl who presented with a choking episode and was found to have an incidental finding of a lung cyst and iron deficiency anemia leading to the diagnosis of pleuropulmonary blastoma (PPB) and a jejunal hamartoma. Our patient is the eighth that has been reported with the association of PPB with jejunal hamartoma and the first one in the radiological literature. PPB is the pulmonary analog of other dysontogenetic neoplasms in childhood. A biological sequence has been described with the three types of PPB to be interrelated as part of pathologic progression. PPB can be associated with other cysts and/or neoplasms in different organs. PPB is part of a hereditary neoplasia predisposition syndrome in up to 40% of cases. Mutations in DICER gene have been described with PPB. Hence, a pediatric patient diagnosed with PPB should be screened for associated conditions during childhood and adolescence including intestinal polyps. Obtaining family history for other neoplasms or cysts is important information that should raise the possibility of PPB in pediatric patients with cystic lung lesions. The presence of this syndrome should alert the clinician to screen and follow up patients and their relatives.